Computed Tomography Characteristics of the Acetabulum in Developmental Dysplasia of the Hip - Poyraz, Ahmet Kursad; Onur, Mehmet Ruhi; Eroglu, Yesim; Gurger, Murat; Goktekin, Mehmet Cagri; Akgol, Gurkan (Kowsar Publ, 2019)
Background: Low-dose computed tomography (CT) is the preferred method for post-reduction evaluation of hips of infants in spica casts, but the assessment of acetabular morphological features in developmental dysplasia of the hip (DDH) using CT has not be done before. Objectives: To determine CT imaging characteristics of the acetabulum in DDH and to be able to determine DDH in pelvic CT examinations performed for different purposes. Patients and Methods: CT images of 102 consecutive patients with DDH (90 females,12 males) and 51 age-matched controls (26 females, 25 males) were included in this study. Acetabular shape abnormalities, surface irregularity, subcortical sclerosis, shallowing, and measurement of acetabular cortical bone thickness were evaluated in coronal reformatted images. Differences in the cortical thickness of dysplastic and normal hips were assessed. Results: Forty-four patients (43.1%) had unilateral and 58 had bilateral DDH (56.9%). Acetabular margin irregularity was present in all patients with unilateral DDH and 55 of the 58 patients with bilateral DDH (94%). Thickening on the inferior part of the ilium compared to the normal side was seen in 41 of the 44 unilateral DDH patients (93%). In the 44 patients with unilateral DDH, the mean cortical thickness measured from the central part of the acetabulum was 0.86 +/- 0.03 mm and 0.65 +/- 0.03 mm on the normal and dysplastic sides, respectively (P = 0.0 001). This difference was more distinct at the acetabular rim, measuring 1.11 +/- 0.06 mm and 0.70 +/- 0.04 mm on normal and dysplastic sides, respectively (P = 0.0 001). Conclusion: Acetabular marginal irregularity and flattening is a reliable finding in the diagnosis of DDH when combined with thickening on the inferior part of ilium and will help in the diagnosis of DDH in patients older than 6 months old with a pelvic CT scan due to diseases other than DDH.
Keywords: Developmental Dysplasia of the Hip; Computed Tomography; Acetabulum; Ultrasound; Margin